(untitled) (Progress Annals: Journal of Progressive Research, 2025)
Infectious intestinal diseases, in particular, diarrhea, are common among children.The radical social and economic changes taking place in our republic in recent years have led to a slight decrease in the number of infectious diseases among children. Acute intestinal diseases occupy the leading place in the pathology of infectious diseases in children. The age of children is of great importance in the structure of acute intestinal diseases. Shigellosis is widespread in children over 1 year of age, followed by salmonellosis, enteroinvasive escherichiosis, rotavirus diarrhea, and others.